Quantitative analysis of the nutrient uptake by Lake Redstone (Sauk Co., Wis.) - Popple, Roger D. (My University, 1972)
Water was collected at four sites and analyzed for amonium nitrogen, nitrate nitrogen, ortho phosphate, pH, temperature and turbidity. Volume of inflow and outflow water was also determined. Lake Redstone received 5,250 kg of nitrate nitrogen, 3,525 kg of ammonium nitrogen and 1,680 kg of ortho phosphate. Of this, 1,030 kg of nitrate nitrogen, 1,150 kg of ammonium nitrogen and 830 kg of ortho phosphate was retained by the lake. This represented a filtering efficiency of 19.66% for nitrate nitrogen, 32.62% for ammonium nitrogen, and 49.49% for ortho phosphate removed from the inflow waters. Lake Redstone also received 111.3 metric tons of sediments during the test period. Of this, 79.3 metric tons of sediments were retained by the lake. This represented a filtering efficiency of 71.0% removal of sediments from the inflow waters.
Keywords: Freshwater biology -- Wisconsin; Limnology -- Wisconsin; Redstone, Lake (Sauk County, Wis.)